Expression of ACE2 and a viral virulence-regulating factor CCN family member 1 in human iPSC-derived neural cells: implications for COVID-19-related CNS disorders - Yoshitaka Kase; Hideyuki Okano (BMC, 2020)
Abstract It has been reported that coronavirus disease 2019 (COVID-19) causes not only pneumonia but also systemic inflammations including central nervous system (CNS) disorders. However, little is known about the mechanism that triggers the COVID-19-associated CNS disorders, due to the lack of appropriate experimental systems. Our present study showed that angiotensin-converting enzyme-2 (ACE2), a cellular receptor for SARS-CoV-2, is expressed in human induced pluripotent stem cell (iPSC)-derived neural stem/progenitor cells (hiPSC-NS/PCs) and young neurons. Furthermore, together with database analysis, we found that a viral virulent factor CCN family member 1 (CCN1), which is known to be induced by SARS-CoV-2 infection, is expressed in these cells at basal levels. Considering the role of CCN1 which is known to be involved in viral toxicity and inflammation, hiPSC-NS/PCs could provide an excellent model for COVID-19-associated CNS disorders from the aspect of SARS-CoV-2 infection-ACE2-CCN1 axis. In addition, we identified compounds that reduce CCN1 expression. Collectively, our study using hiPSC-NS/PCs may aid in the development of a therapeutic target for COVID-19-related CNS disorders.